Is there any causal effect between animal welfare and farm economic performance? Evidence from Finnish dairy farms - Ait Sidhoum, Amer; Niemi, Jarkko K (Oxford University Press, 2025)
This paper explores the relationship between animal welfare and economic outcomes in agriculture, focusing on whether improvements in animal welfare translate into better farm performance. Specifically, it examines a composite animal welfare index integrating multiple animal-based indicators and its association with milk revenue among Finnish dairy farms over the period 2010–2017. Utilizing multiple econometric approaches, including cross-sectional and panel data regressions, the study reveals a complex and heterogeneous relationship. While a negative association between poorer welfare and milk revenue is evident in cross-sectional estimations, this relationship weakens and generally loses statistical significance once farm-specific fixed effects are included, indicating that much of the association reflects structural or management differences rather than a direct causal effect. The findings underscore the importance of distinguishing correlation from causation when designing and interpreting animal welfare-related policies. Beyond policy relevance, the paper contributes to the limited empirical evidence on causal linkages between animal welfare and farm economic performance.
Keywords: animal welfare; economic outcomes; dairy farms; finland; econometrics